PENCITRAAN DALAM PUISI HUJAN YANG MENGIRIM DINGIN KARYA SIGIT EMWE: KAJIAN SEMANTIK - Mofu, Hengki (Universitas Papua, 2018)
The title of this research is Pencitraan dalam Puisi Hujan yang Mengirim Dingin (HMD), Sigit Emwe’s work: Semantic study uses qualitative research paradigm. The aim of the research is to describe imaging in the poem using semantic approach (lexical and connotative). The data of the research is secondary data brought from Pilar Penyair Obsesi Press 2011. The analysis begins from the lexical and connotative interpretation. It focuses on all of the words that contain imaginary characteristic. Based on the study, HMD’s poem contains visible, audio, touch, and kinesthetic imaging. Visual imaging is signed by using some words such as to see, to look at, and to use eyes. Audio imaging is signed by using words sound of rain, silent in jail. Touch imaging is signed by using word cold. Kinesthetic imaging is signed by using phrase such as the walls of the room prevents the voice of rain. Rain still walks patiently, and rain does not move from the porch, lexically the word rain in this title means raindrop which falls down to the earth because of evaporating process. This is a natural process. Connotatively, rain is associated as tears of a son which is falling down because of the rules of his family that shackle his life. Semantically this title contains happiness and sadness. Therefore the happiness and the sadness are two things which are worthy and humane.